Using data envelopment analysis to evaluate the efficiency of creative tourism in Portugal - Mansour Ghanian; Paula Remoaldo (Tourism & Management Studies)
This paper presents an indicator system for evaluating Creative Tourism activities developed in four regions of Portugal through CREATOUR’s pilot projects. It is a quantitative study based on primary and secondary sources. Data Envelopment Analysis (DEA) was used to evaluate the efficiency of those projects as decision-making units (DMUs). Data analysis was performed using Excel and EMS software. The results show that the overall level of tourism efficiency is relatively high, and most pilots in each region have full efficiency. However, there is still room for improvement in some of them. Based on the results of this study, Portuguese creative tourism professionals need to pay more attention to social capital and job creation as the factors that have the greatest impact on improving efficiency. This is the first study to assess the effectiveness of a pilot project in creative tourism. Therefore, the results of this study can pave the way for implementing Creative Tourism projects in other parts of the world.